Earthquakes Sources Parameter Estimation of 20080917 and 20081114 Near Semangko Fault, Sumatra Using Three Components of Local Waveform Recorded by IA Network Station - Santosa, Bagus Jaya; Madlazim, Madlazim (UI Scholars Hub, 2012)
The 17/09/2008 22:04:80 UTC and 14/11/2008 00:27:31.70 earthquakes near Semangko fault were analyzed to identify the fault planes. The two events were relocated to assess physical insight against the hypocenter uncertainty. The data used to determine source parameters of both earthquakes was three components of local waveform recorded by Geofon broadband IA network stations, (MDSI, LWLI, BLSI and RBSI) for the event of 17/09/2008 and (MDSI, LWLI, BLSI and KSI) for the event of 14/11/2008. Distance from the epicenter to all station was less than 5°. Moment tensor solution of two events was simultaneously analyzed by determination of the centroid position. Simultaneous analysis covered hypocenter position, centroid position and nodal planes of two events indicated Semangko fault planes. Considering that the Semangko fault zone is a high seismicity area, the identification of the seismic fault is important for the seismic hazard investigation in the region.